99 AN UNUSUAL CAUSE OF IRON DEFICIENCY ANEMIA. Issue 1 (1st January 2007) - Kale, S. S.; Sachdev, M. S.; Ismail, M. K.; Tombazzi, C.
Abstract : Case: A 61-year-old African American (AA) female presented with a chief complaint of melena, fatigue, and inability to eat, which has been getting progressively worse for 2 years. She also complained of early satiety and left shoulder pain. Her past history was significant for Bell's palsy a number of years ago and one syncopal episode 2 months ago for which she did not seek medical attention. Examination was significant for conjunctival pallor, a II/VI systolic murmur at the left upper sternal border, and a large firm mass in the left upper quadrant of the abdomen that appeared to be coming from under the ribs. Laboratory tests revealed a microcytic hypochromic anemia, thrombocytosis, and iron deficiency. CT of the abdomen revealed a large mass in the abdomen that was approximately 19 × 20 × 16 cm that was coming from the stomach. Upper endoscopy was performed and revealed a tubular stomach with a large 5 cm umbilicated mass in the fundus that was ulcerated and oozing blood. Endoscopic biopsy was negative for malignancy, and a CT-guided biopsy was performed of the abdominal mass, which stained positively for C-Kit, consistent with the diagnosis of gastrointestinal stromal tumor (GIST). Discussion: GIST is a mesenchymal tumor of the GI tract that is more common in men between the ages of 40 and 80. Sixty percent of these tumors occur in the stomach and 70% are symptomatic, usually presenting as GI blood loss. The diagnosis can be made endoscopically as an incidental finding or by CT. It is confirmed via histology and immunochemical staining. The tumor is positive for CD117 antigen (aka C-KIT). The tumor has three distinct morphologies, with a majority being of the spindle cell variety. The tumor metastasized to the liver a majority of the time. The treatment has historically been surgical resection; however, the chemotherapeutic agent, imatinib, has shown excellent results, and when used with surgery, the 2-year survival is over 70%. Conclusion: GIST is an unusual tumor that can present as melena with iron deficiency anemia. It is a rare tumor but should be included in the differential diagnosis when working up melena and iron deficiency anemia.